Haemophagocytic lymphohistiocytosis presenting as liver failure following Epstein-Barr and prior hepatitis A infections. (13th August 2013) - Pinto-Patarroyo, Gineth Paola; Rytting, Michael E; Vierling, John Moore; Suarez-Almazor, Maria E
Abstract : Haemophagocytic lymphohistiocytosis (HLH) is associated with high mortality even after prompt diagnosis. We present a young man with HLH triggered by two common viral diseases, infectious mononucleosis and hepatitis A. This patient presented with fever, rapidly progressive liver failure, anasarca and cholestasis, followed by anaemia and neutropenia. His carbohydrate antigen 19-9 reached over 9000 U/mL. Initial bone marrow and liver biopsies did not show histological features of malignancy or HLH. The patient was finally diagnosed and treated almost 1 year after the initial symptoms started, and had an excellent response with etoposide and dexamethasone. This case is unusual because it was triggered following mononucleosis in a patient with positive total antibodies against hepatitis A, with rapidly developing liver failure, and also because the patient's response was excellent despite the delay in treatment. It underscores the importance of suspecting HLH when severe systemic illness develops after a viral infection, even in the absence of clear histological features.